The Nature and Practice of Trust - Cohen, Marc A. (Taylor & Francis, 2023)
Marc Cohen, trust, philosophy of trust, trustworthiness, moral relationships, therapeutic trust, generalized trust, obligations, calculativeness, commitments, intrinsic goods, moral psychology, social philosophy